Citizen Science and Traditional Ecological Knowledge—Values of Inclusion in the Wabanaki Youth Science Program - carr, tish; Ranco, Darren (Maine Policy Review, 2017)
tish carr and Darren Ranco describe the Wabanaki Youth Science Program (WaYS) and how it strives to incorporate traditional ecological knowledge with Western science.
Keywords: citizen science; traditional ecological knowledge; TEK